Assertive outreach for "difficult to engage" patients: A useful tool for a subgroup of patients in specialized early psychosis intervention programs. (30th May 2016) - Alameda, Luis; Golay, Philippe; Baumann, Philipp; Morandi, Stéphane; Ferrari, Carina; Conus, Philippe; Bonsack, Charles
Abstract: Purpose: Most specialized Early Psychosis (EP) programs include assertive outreach (AO) principles, either for all patients or as an intensive case management (ICM) subprogram in selected situations. The objective of this study is to examine prevalence, characteristics and outcomes of patients who needed additional ICM in a specialized EP program. Methods: In a 3-year prospective naturalistic study of 229 consecutive EP patients treated at TIPP-Lausanne we compared characteristics of those who needed ICM and those who did not. Results: 60 (26.2%) TIPP patients needed ICM. At baseline, ICM-patients showed a poorer academic premorbid functioning (p=0.019); lower level of insight (p<0.001); had a previous history of alcohol (p=0.043) and cannabis (p=0.040) use. ICM-patients were less likely to be adherent to medication during the early phase of treatment but differences disappeared during follow-up. ICM-patients showed globally a poorer functional level and higher level of positive and negative symptoms during the follow-up. Conclusions: About one quarter of EP patients needed a combination of ICM and assertive outreach. Despite the high treatment adherence in both groups, psychotic symptoms remained higher in ICM-patients. In a real live setting with limited resources, combination of ICM and AO in selected situations seems a valid solution. Highlights: 60 of the 229 EP patients were considered as difficult to engage (DTE) and had been offered addition of ICM to standard CM. DTE patients showed a poorer premorbid and clinical profile at baseline compared to the other EP patients. DTE patients can reach good levels of engagement and adherence to treatment when treated with ICM during follow-up. Despite of this, psychotic symptoms remained higher in DTE patients, suggesting the need for adapted interventions.